2021
DOI: 10.30565/medalanya.808806
|View full text |Cite
|
Sign up to set email alerts
|

Prokalsitonin, D-Dimer, Ferritin, Troponin ve Laktat Düzeylerinin COVID-19 Hastalığı ile İlişkisi

Abstract: Amaç: Koronavirüs hastalığı-2019 hastalarında enflamasyon artışı veya pıhtılaşma bozukluğu artışı görülebilmektedir. Bazı biyobelirteçlerin, hastaneye yatış yapılmasında belirleyici olabileceği düşünülmektedir. Bu çalışmadaki amacımız, serum prokalsitonin, troponin, D-dimer, ferritin ve laktat düzeyleri ile Koronavirüs hastalığı-2019 arasındaki ilişkiyi araştırmaktı. Metod: Koronavirüs hastalığı-2019 şüphesi olan, kan biyokimya ve kan gazı tetkikleri çalışılan hastalar çalışmaya dahil edildi. Polimeraz zincir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
1
1
Order By: Relevance
“…Ferritin levels due to secondary hemophagocytic lymphohistiocytosis and cytokine storm syndrome seen in severe COVID-19 patients are much higher and indicate a poor prognosis [1]. In the study conducted by Sahin et al, it was determined that there was no statistically significant difference in ferritin levels between hospitalized and non-hospitalized patients [39]. Contrary to the literature, the ferritin level was high in hospitalized patients in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…Ferritin levels due to secondary hemophagocytic lymphohistiocytosis and cytokine storm syndrome seen in severe COVID-19 patients are much higher and indicate a poor prognosis [1]. In the study conducted by Sahin et al, it was determined that there was no statistically significant difference in ferritin levels between hospitalized and non-hospitalized patients [39]. Contrary to the literature, the ferritin level was high in hospitalized patients in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…It has been shown that 14%-29% of patients with COVID-19 pneumonia required intensive care [ 8 ]. The disease has high mortality in the elderly and people with comorbidities; however, it can also cause severe clinical pictures in young people without comorbidities [ 9 ]. To prevent mortality, early detection of patients who require aggressive treatment is very important [ 10 ].…”
Section: Introductionmentioning
confidence: 99%